Aplikasi Manajemen BK untuk Meningkatkan Disiplin Belajar Siswa - Matondang, Fatiha Sabila Putri; Firman; Neviyarni (Education & Learning, 2022)
BK management is all efforts or methods used by school principals to optimally utilize all components or resources (manpower, funds, facilities and infrastructure) and information systems in the form of a collection of guidance data to provide Guidance and Counseling services in order to achieve goals. In the management of Guidance and Counseling, BK teachers and school BK coordinators have made plans that must be implemented, evaluated, analyzed and followed up which contain BK services to improve student learning discipline. Student learning discipline will create a good atmosphere and student learning process in order to achieve the goals of Guidance and Counseling as well as educational goals. The better the management of Guidance and Counseling in schools, the goals can be achieved optimally. Therefore, there is a need for good cooperation between Guidance and Counseling teachers and all school personnel, especially with the principal in making BK management in schools, not only good cooperation but also skills in carrying out the responsibilities of each teacher.